Effects of Mobile-Learning in a flipped classroom Model on Non-English-Majored Graduates in Graduate English - Lou, Yougen; Sun, Yongqiang (IJRDO- Journal of Educational Research, 2018)
This paper reviewed a one-term experiment on mobile-learning(M-learning) in a flipped classroom model in teaching the curriculum Graduate English to 122 first-year non-English-majored graduate students majored agriculture, plant protection, floriculture, history, economics, business and veterinary from Yangtze University as participants. Participants in this study consisted of 61 non-English-majored graduate students in the control group (CG) and 61 non-English-majored graduate students in the treatment group (TG). The process of mobile-learning(M-learning) in a flipped classroom model in teaching the course Graduate English was divided into the three parts: M-learning outside of a flipped classroom, M-learning in-class of a flipped classroom and M-learning outside of a flipped classroom. The results showed that 1) compared with a teacher-dominated approach for CG, M-learning in a flipped classroom mode, student-centred approach, in teaching the course Graduate English for TG did a better job in enhancing students’ ability applied in Graduate English; 2) there were significant differences between males in CG and TG, and females in CG and TG; 3) participates in TG hold positive opinions towards mobile-learning in a flipped classroom model.